Human Rights and Business: Human Rights Violations in the Outsourcing Industry in Modern Business Indonesia - Arifin, Saru (JILS (Journal of Indonesian Legal Studies), 2021)
This article analyzes outsourcing job practice in contemporary business activities in Indonesia, focusing on types and factors that contribute to human rights abuse in the outsourcing business, based on academic literature and regulations on business and human rights. In today's Indonesian labor market, outsourcing jobs are a kind of phantom. Laborers risked not receiving adequate wages, work insurance, or equal bargaining power with the outsourcing company under this job recruitment system. Laborers' associations protested almost every May Day moment, demanding that the outsourcing job system be abolished. They also demanded to be hired directly by the company rather than by the outsourcing firm. Unfortunately, the government responded to the demand by enacting the Workforce Act No. 13 of 2013. This law endorsed outsourcing with specific requirements that provide clear guidance for both employers and employees. However, in practice, companies frequently break outsourcing roles by hiring workers to staff their core business activities. On the other hand, outsourcing corporations also violate the Act's basic rights for outsourcing laborers. As a result, it implies human rights violations. Laborers were frequently threatened with losing their right to a healthy working environment, being fired from their contract without consultation, and having their fundamental rights violated. Human rights violations in outsourcing job activities are primarily caused by a lack of government oversight and law enforcement.